Kandungan Mineral Arbila (Phaseulus lunatus L.) Sebagai Pakan Pada Tanah Vertisol dengan Penambahan Bokashi Berbahan Chromolaena odorata dan Feses Sapi - Agrifina Risti Tae; Bernadete Barek Konten; Agustinus Semang; Redempta Wea; Abner Tonu Lema (Politeknik Negeri Jember, 2019)
This study aimed to evaluate the mineral content of arbila for the administration of bokashi based on Chromolaena odorata and faeces on the advertisol soil. Field trials had been carried out for 5 months in the villange of Noelbaki, and analysis of this plant in the Food Chemistry Laboratory Hassanuddin University, Makassar. This study was designed based on a complete randomized design (CDR) with 5 treatments, and 4 replications. Plants were planted on the advertiser soil in polybags. The treatments were the level of organic fertilizer (bokashi) i.e. B0=without bokashi B10=10 ton/Ha, B20=20 ton/Ha, B30=30 ton/Ha, B40=40 ton/Ha. Bokashi level was changed to polybag as followed, B0=without treatment, B10=75 g/polybag, B20=150 g/polybag, B30=225 g/polybag, B40=300 g/polybag. The variables observed the mineral content of calcium, phosphorus and magnesium. Bokashi level had a very significant effect on phosphorus and magnesium content, but had not a significant effect on calsium content. The percentage of calsium content was 0.75%, and the average of each treatments were B0 and B10=0.56%, B20=0.58%, B30=0.61%, B40=0.55%. The average of phosphorus content for each treatments were B0=0.15%, B10=0.21%, B20=0.18%, B30=0.16%, and B40=0.23%. The average of magnesium content for each treatments were B0=0.15%, B10=0.18%, B20=0.27%, B30=0.32%, and B40=0.37%. It was concluded that the levels of organic fertilizer (bokashi) had a significant effect on the percentage of phosphorus and magnesium but did not have a significant effect on the calcium content of arbila forage.